Bending Performance of Half-Slab Styrofoam Mortar with Glazed Nylon Fiber - Solikin, M. (Sciendo, 2021)
This paper scrutinizes bending performance of light weight half-slab mortar against bending and punching load. To produce the slab, 30 round bud Styrofoam was used as fine aggregate substitution. Besides, glazed nylon fiber was applied to increase its tension strength and cavities at tension area of slab were also created. This method results in the significant reduction of self-weight of half-slab, while the cavities do not affect its bending performance and the fiber increases its ductility. Furthermore, the lower result of punching test should not to be a disadvantage as the slab is primarily to be used as a formwork. Â© 2021 Mochamad Solikin et al., published by Sciendo 2021.